2015
DOI: 10.1039/c4fo00834k
|View full text |Cite
|
Sign up to set email alerts
|

Infusions of artichoke and milk thistle represent a good source of phenolic acids and flavonoids

Abstract: Cynara scolymus L. (artichoke) and Silybum marianum (L.) Gaertn (milk thistle) are two herbs well-known for their efficiency in the prevention/treatment of liver injuries, among other chronic diseases. Therefore, the aim of this work was to characterize specific bioactive components, phenolic compounds, in hydromethanolic extracts but also in infusions (the most commonly used preparations) obtained from the whole plant of milk thistle and artichoke. The phenolic profiles were accessed using HPLC-DAD-MS/ESI. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Compound 5 ([M − H] − at m / z 623) MS 2 fragments revealed the alternative loss of hexosyl ( m / z at 461; −162 u) and glucuronyl ( m / z at 285; −176 u) residues, indicating location of each residue on different positions of the aglycone. No information about the identity of the sugar moieties and location on the aglycone could be obtained, so, the compound was identified as luteolin- O -hexosyl- O -glucuronide [ 20 ]. Compound 6 ([M − H] − at m / z 463) was identified as a eriodictyol derivative, due to its UV-Vis spectra and MS fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 5 ([M − H] − at m / z 623) MS 2 fragments revealed the alternative loss of hexosyl ( m / z at 461; −162 u) and glucuronyl ( m / z at 285; −176 u) residues, indicating location of each residue on different positions of the aglycone. No information about the identity of the sugar moieties and location on the aglycone could be obtained, so, the compound was identified as luteolin- O -hexosyl- O -glucuronide [ 20 ]. Compound 6 ([M − H] − at m / z 463) was identified as a eriodictyol derivative, due to its UV-Vis spectra and MS fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds with peak numbers 2-8, 10, 11 and 13 have been previously reported in the literature in different artichoke samples. 3,5,11,33,35,36 Compounds with peak numbers 1 and 9 were identified as the cis form of hydroxycinnamoyl derivatives, since these would be expected to elute before the corresponding trans ones, as observed after UV irradiation (366 nm, 24 h), of hydroxycinnamic acids in our laboratory. 37 cis and trans isomers of 3-O-caffeoylquinic acid (compounds with peak numbers 1 and 2) and 3,5-O-dicaffeoylquinic acid (compound with peak numbers 9 and 10), as all the hydroxycinnamoyl derivatives identified, were distinguished and identified by typical fragmentation patterns as described by Clifford et al 28,29 To the best of our knowledge, compound with peak number 12 is reported for the first time in artichoke leaves and is tentatively identified as succinoyl-di-O-caffeoylquinic acid, taking into account the fragmentation pattern reported by Jaiswal and Kuhnert.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Crop by-products represent about 80% of total biomass, they are also rich sources of phenolic compounds and are usually used as herbal medicines, either as infusions and herbal preparations or as ingredients in dietary supplements for hepatic and other diseases. [3][4][5] Leaves and stems of artichoke present significant antioxidant activity, [6][7][8] and for this purpose they are the main ingredients in many dietary supplements and drugs. In particular, leaves are the most common plant part used for therapeutic purposes, since they have numerous medicinal properties including antitumor, antioxidant, antibacterial, antifungal, and hepatoprotective effects and so forth, mostly attributed to their high content of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the oil extracted from milk thistle seeds can be used in the anticholesterol diets for cardiovascular disease prevention (El-Mallah et al, 2003) as it constitutes a good source of unsaturated fatty acids (56% polyunsaturated and 21% monounsaturated) (Yin et al, 1998), vitamin E (50e60 mg/100 g) (Hadolin et al, 2001), phenolic compounds and flavonoids (0.25%) (Li et al, 2012;Pereira et al, 2015;Wallace et al, 2003). In addition, milk thistle seeds contain active compounds such as silymarin.…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin has been known since centuries and recommended in traditional European and Asian medicine, mainly for treatment of liver disorders (Hadolin et al, 2001). These seeds contain silymarin complex, which consists of four flavonolignans (Pereira et al, 2015;Wallace et al, 2003): silychristin (SCN), silydianin (SDN), silibinin (SBN) and taxifolin (TXF) Fig. 1.…”
Section: Introductionmentioning
confidence: 99%